Cyrtodactylus rufford, a new cave-dwelling bent-toed gecko (Squamata: Gekkonidae) from Khammouane Province, central Laos - Luu, Vinh Quang; Calame, Thomas; Nguyen, Truong Quang; Le, Minh Duc; Bonkowski, Michael; Ziegler, Thomas (Zootaxa, 2016)
We describe a new species of the gekkonid genus Cyrtodactylus from Khammouane Province, central Laos based on morphological and molecular data. Morphologically, Cyrtodactylus rufford sp. nov. differs from its congeners by a unique combination of the following characters: medium size, SVL reaching 72.5 mm; dorsal pattern with three or four light transverse bands between limb insertions; one intersupranasal; 14–16 irregular dorsal tubercle rows at midbody, weakly developed in the paravertebral region; 27–29 ventral scale rows between ventrolateral folds; 42–43 precloacal and femoral pores in a continuous row in males, enlarged femoral and precloacal scales present; 4 or 5 postcloacal tubercles on each side; dorsal tubercles present at base of tail; medial subcaudal scales enlarged. Molecular analyses show that the new species is closely related to C. khammouanensis, which was originally described from Khammouane Province.